Gendered work-family life courses and late-life physical functioning: A comparative analysis from 28 European countries. (September 2022) - Uccheddu, Damiano; Emery, Tom; Gauthier, Anne H.; Steverink, Nardi
Abstract: Combining work and family roles can have beneficial consequences on health but could also result in chronic stress and adverse health outcomes at older ages. This study aimed to examine combined employment, parenthood, and partnership histories of men and women during the childbearing period (ages 15-49), and to investigate the links of these work and family roles with physical functioning later in life. We used data from the Survey of Health, Ageing and Retirement in Europe (SHARE) with retrospective information on employment, parenthood, and partnership histories for 18, 057 men and 20, 072 women (n = 38, 129) living in 28 different countries belonging to six European welfare clusters. We applied multichannel sequence analysis (MCSQA) and hierarchical clustering to group work-family trajectories into 12 clusters for men and 15 clusters for women. We assessed the association between work-family life courses and grip strength by estimating multivariable linear regression models. Delayed work and family transitions, unstable employment, and the absence of combinations of work and family roles between age 15 and 49 were associated with weaker grip strength in later life for both men and women. Results differed by gender and were framed by the welfare context in which gendered work and family responsibilities unfold across individual life courses. The findings make an important contribution to the domain of gender and health in later life and stress the need to engage more with issues related to the mechanisms linking work and family trajectories to poor health in later life. Highlights: Adverse combinations of work-family circumstances are associated with reduced physical functioning. The impact of work and family trajectories varies by gender and welfare arrangement. Gaps are wider in countries lacking reconciliation policies for work and family life.